HUMAN CAPITAL, STRUCTURAL CAPITAL, DAN CAPITAL EMPLOYED TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR: ANALISIS INTELLECTUAL CAPITAL DENGAN PENDEKATAN VALUE ADDED - Erni Indriyana; Munawaroh (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This study aimed to assess the impact of Intellectual Capital, including Human Capital, Structural Capital, and Capital Employed on Financial Performance using a value-added approach. Purposive sampling was used to select 32 Manufacturing Companies in the Food and Beverage Subsector's Primary Consumer Sector, listed on the Indonesia Stock Exchange between 2019 and 2021. Regression tests demonstrated a significant and positive influence of Intellectual Capital and Structural Capital on Financial Performance, while other factors showed negative effects. The implications of this research are that investors hope that this Intellectual Capital factor becomes part of other factors that need to be considered before investing their funds.